Cell type specific adhesion to surfaces functionalised by amine plasma polymers - Černochová, P; Blahová, L; Medalová, J; Nečas, D; Michlíček, M; Kaushik, P; Přibyl, J; Bartošíková, J; Manakhov, A; Bačáková, L; Zajíčková, L (Scientific reports, 2020)
Our previously-obtained impressive results of highly increased C2C12 mouse myoblast adhesion to amine plasma polymers (PPs) motivated current detailed studies of cell resistance to trypsinization, cell proliferation, motility, and the rate of attachment carried out for fibroblasts (LF), keratinocytes (HaCaT), rat vascular smooth muscle cells (VSMC), and endothelial cells (HUVEC, HSVEC, and CPAE) on three different amine PPs. We demonstrated the striking difference in the resistance to trypsin treatment between endothelial and non-endothelial cells. The increased resistance observed for the non-endothelial cell types was accompanied by an increased rate of cellular attachment, even though spontaneous migration was comparable to the control, i.e., to the standard cultivation surface. As demonstrated on LF fibroblasts, the resistance to trypsin was similar in serum-supplemented and serum-free media, i.e., medium without cell adhesion-mediating proteins. The increased cell adhesion was also confirmed for LF cells by an independent technique, single-cell force spectroscopy. This method, as well as the cell attachment rate, proved the difference among the plasma polymers with different amounts of amine groups, but other investigated techniques could not reveal the differences in the cell behaviour on different amine PPs. Based on all the results, the increased resistance to trypsinization of C2C12, LF, HaCaT, and VSMC cells on amine PPs can be explained most probably by a non-specific cell adhesion such as electrostatic interaction between the cells and amine groups on the material surface, rather than by the receptor-mediated adhesion through serum-derived proteins adsorbed on the PPs.
Keywords: plazmové plyny; buněčné linie; polymery; Amines; Plasma Gases; Polymers; buněčná adheze; Humans; povrchové vlastnosti; Cell Line; Cell Adhesion; lidé; aminy; Surface Properties